Determination of Trans-Fatty Acid Levels in Selected Syrian Food Products - Radwan Badr Al-Deen; Bassam Al-Oklah; Mohamad Alshehabi; Tahani Al-idee (Syrian Journal for Science and Innovation)
Trans fatty acid (TFA) consumption correlates with negative health effects and contributes significantly to morbidity and mortality worldwide. The current study aimed to determine the levels of trans fatty acids (TFAs) and conjugated linoleic acid (CLA) in some Syrian food products to develop a TFAs composition database that would provide authorities with information on TFAS levels in Syrian food. In 2022, eighty-three samples were collected from Damascus city's local market, including cow’s ghee (n=9), palm oil (n=7), sardine (n=9), olive oil (n=30, some of them are bottled in glass or plastic bottles and the others from local olive presses), soybean oil (n=7), sunflower oil (n=7), flaxseed oil (n=5), and sesame oil (n=2). The Soxhlet method was used to extract the lipids from the samples (except oils), then the methyl esters of fatty acids (FAME) were prepared and the concentration of fatty acids (g/100g) was determined using gas chromatography (GC) equipped with a Split/Splitless injector and a flame ionization detector (FID). The results revealed that the levels of Trans fatty acids (TFAs) ranged in all samples from 0.04 to 1.82 g/100g, with high amounts (4.78%) found in one sample of cow’s ghee, two samples of palm oil, and one sample of soybean oil. The olive oil, Flaxseed oil, sesame oil, and sardine contained less than 1 g TFAs/100g. Compared with the other samples, cow’s ghee showed the highest CLA concentration (0.60 g/100g). These findings suggest that additional reductions in Syria are required to properly meet public health objectives and lower the incidence of illnesses such as coronary heart disease.